COVID-19 Illness Severity in the Elderly in Relation to Vegetarian and Non-vegetarian Diets: A Single-Center Experience - Hou, Yi-Cheng; Su, Wen-Lin; Chao, You-Chen (Frontiers in Nutrition, 2022)
The first wave of the coronavirus disease 2019 (COVID-19) outbreak in Taiwan occurred in May 2021. The risk for and severity of this disease varies and is highly dependent on personal habits and comorbidities. Moreover, the gut microbiome, which may be affected by diet, is highly susceptible with regard to the risk and severity of infectious diseases such as COVID-19. The relationship between dietary habits, nutritional status, and the effects of these factors on the immune system in the context of a global pandemic is an extremely important topic of immediate concern. Hence, the aim of this study was to explore the effect of vegetarian and non-vegetarian diets on COVID-19 severity during the pandemic. We conducted a retrospective evaluation of 509 patients who had been diagnosed with COVID-19 at a single medical center between May and August 2021. Patients were divided into three groups according to disease severity. For patients aged ≥65 years, COVID-19 symptom severity was statistically significantly and inversely associated with adherence to a vegetarian diet (p=0.013). Moreover, subgroup analysis results showed that older COVID-19 patients and those with a non-vegetarian diet had a higher risk of contracting critically severe COVID-19 (adjusted OR=5.434, p=0.005). Further research is needed to determine the effects of dietary habits on COVID-19 risk and severity during the global pandemic.